Scientific Journal Publishing Management Training at STikes Abdurahman Palembang Refers to Accreditation Standards - Hendra Prasetyo; Sri Maryati (Indonesian Journal of Community Engagement, 2025)
This community service activity began with the problem of scientific publication which is an obligation for a researcher. Efforts to improve the quality of publishers in managing a scientific journal according to standards are demands and problems experienced by the publisher Altaf Publishing Corp. This Community Service Activity is proposed in the form of mentoring as an effort to increase knowledge in managing scientific journals according to standards. The stages of the activity are carried out through the planning stage, implementation of activities with lecture and discussion methods, and the last stage is evaluation of the activity. The results of the activity provide increased knowledge and skills of journal managers, especially for preparation in standardizing journal management towards journal ccreditation. The mentoring activities carried out are very important because they can provide increased knowledge in managing journals according to the problems faced by Community Service partners.